Dietary Exposure to Aflatoxins in Some Randomly Selected Foods and Cancer Risk Estimations of Cereals Consumed on a Ghanaian Market - Nii Korley Kortei; Theophilus Annan; Seidu A. Richard; Adjoa A. Boakye; Clement O. Tettey; Edward Ken Essuman; Enoch Aninagyei; Precious Agbemeseli (Journal of Food Quality)
Aflatoxins have gained so much reputation among all mycotoxins due to their notoriety in causing countless adverse health effects on humans as well as animals. It continues to be a major concern in food safety globally. In this study, total and constitutive aflatoxins levels as well as the carcinogenic risks posed by 110 food and feed samples (55 cereals, 20 nuts and oils, 18 animal feed, and 18 fruits and vegetables) collected from the Ho Central market in the Volta region, Ghana, were assessed. Using high-performance liquid chromatography connected to a fluorescent detector (HPLC-FLD), levels of total aflatoxins (AFtotal) and aflatoxins constituents, namely, AFB1, AFB2, AFG1, and AFG2, were analyzed. By using the model prescribed by Joint FAO/WHO Expert Committee on Food Additives (JECFA), the risks posed by the food and feed samples were determined. The degrees of toxicity were in the ranges of 0.78–234.73 μg/kg, 0.47–21.6 μg/kg, 1.01–13.75 μg/kg, and 0.66–5.51 μg/kg, respectively, for AFB1, AFB2, AFG1, and AFG2. Out of the samples analyzed for AFtotal, about 51 (46.4%) exceeded the limits of GSA and were in the range 10.63 ± 1.20–236.28 ± 4.2 μg/kg. While for EFSA, 71 (64.54%) exceeded and ranged between 4.72 ± 0.28 and 236.28 ± 4.2 μg/kg. Furthermore, estimated daily intake (EDI) of 27.10–283.70 ng/kg·bw/day, margin of exposure (MOE) of 1.409–14.76, average potency of 0–0.00396 ng aflatoxins/kg·bw/day, and cancer risks with a range of 0.107–1.122 cases/100,000 person/yr were observed. Taken together, it could be concluded that consuming cereals pose adverse effects on human health regardless of the age of the consumer.